Manet's modernism, or the face of painting in the 1860s - Fried, Michael 1939- (Univ. of Chicago Press, 1996)
By placing the painter squarely within his generation (along with Henri Fantin-Latour, Alphonse Legros, and James McNeill Whistler, all of whom are treated at length) as well as in the context of the art-critical discourse of his time, Fried transforms our sense of Manet's artistic project. Instead of the usual emphasis on flatness and visuality, Fried focuses on aspects of Manet's work that have either been minimized or ignored: his repeated allusions to Old Master sources, his desire for "universality" as regards both national schools and individual genres, his efforts to annul the absorptive basis of the modern French tradition, his invention of a sort of portrait-tableau, above all his pursuit of facingness and strikingness as means of reconstructing the relationship between painting and beholder